2014
DOI: 10.1038/ejcn.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Eating frequency is inversely associated with blood pressure and hypertension in Korean adults: analysis of the Third Korean National Health and Nutrition Examination Survey

Abstract: This study suggests that lower EF is significantly associated with higher BP, which may be partially mediated by the effect of central obesity. Further prospective studies are needed to verify this causal relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 38 publications
1
36
0
2
Order By: Relevance
“…The majority of the studies were conducted in the USA (6,9,12,13,15,17,(24)(25)(26)(27)(28) and European countries (8,10,24,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) . Two studies included only men (13,36) , five included only women (32,35,37,39,40) and twenty-four included both sexes (6,(8)(9)(10)(11)(12)14,15,17,(24)(25)(26)(27)(28)(29)(30)(31)33,34,37,38,<...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies were conducted in the USA (6,9,12,13,15,17,(24)(25)(26)(27)(28) and European countries (8,10,24,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) . Two studies included only men (13,36) , five included only women (32,35,37,39,40) and twenty-four included both sexes (6,(8)(9)(10)(11)(12)14,15,17,(24)(25)(26)(27)(28)(29)(30)(31)33,34,37,38,<...>…”
Section: Resultsmentioning
confidence: 99%
“…Seven received quality scores above 70 % (14,15,29,31,39,40,42) . Six studies used a simple question or meal pattern questionnaire to access eating frequency (14,15,31,39,41,42) and three used multiple recalls (27,29,37) . Five studies provided a complete list of (12) 2003-2012 Women and men from NHANES 2003-2012 18 696 ≥60 Cross-sectional Gigante et al (1997) (42) 1994 Brazilian women and men 1035 20-69 Cross-sectional Karatzi et al (2015) (29) NA (15) 1971 -1975 to 1982-1984 Women and men from NHANES I and NHEFS 7147 25-74 Prospective: 8-10year follow-up Holmback et al (2010) (10) 1991 (17) 1994 (40) 2008 American women 1099 40-60 Cross-sectional Smith et al (2012) (11) 2004-2006 Australian women and men 2775 26-36 Cross-sectional Titan et al (2011) (30) 1993 and 1997 Women and men from Norfolk cohort of EPIC 14 666 45-75 Cross-sectional Yannakoulia et al (2007) (32) NA Greek women 64 pre-and 50 postmenopausal 24-74 Cross-sectional Murakami and Livingstone (2014) (38) 2000-2001 British women and men 1487 19-64 Cross-sectional Berg et al (2009) (31) 2001-2004 Swiss women and men 3610 25-74 Cross-sectional Drummond et al (1998) (8) NA Women and men workers of Scotland 95 Mean 20 (SD 55) Cross-sectional Marín-Guerrero et al (2008) (33) 1999 Spanish women and men 34 974 25-64 Cross-sectional Peixoto et al (2007) (43) 2001 Brazilian women and men 1252 20-64 Cross-sectional Ruidavets et al (2002) (36) 1996-1997 French men 330 45-64 Cross-sectional Teichmann et al (2006) (39) NA Brazilian women 981 20-60 Cross-sectional van der Heijden et al (2007)…”
Section: Resultsmentioning
confidence: 99%
“…Although our group and others have previously shown an independent cross-sectional association of eating frequency with hypertension and BP [20][21]23], the clinical utility of meal patterns cannot be further assessed before their predictive value is proven. To the best of our knowledge these are the first prospective results supporting a direct link between eating frequency and development of hypertension and/or target organ damage after a 5-year follow-up period.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, cross-sectional data support this hypothesis. An inverse association between eating frequency and diastolic but not systolic BP has been found in adolescents and with BP and hypertension in adults [20,21]. A single controlled trial revealed that isocaloric consumption of 1 meal/day instead of 3 meals/day significantly increased BP in healthy adults [22].…”
Section: Introductionmentioning
confidence: 99%
“…Eating frequency and nutritional measurements. EF was defined as the sum of the number of meals and snacks eaten per day as previously described (32,33) . Meal frequency was assessed using the following question: 'Did you eat breakfast/lunch/ dinner yesterday?'…”
Section: Measurement Of Variablesmentioning
confidence: 99%